Peran Pengadilan Agama dalam Mewujudkan Efektivitas Konsep Sedekah Bernegara - Faruqi, Ahmad; Syahmedi, Ramadhan (RIO LAW JURNAL, 2024)
Alms is a means provided by Islam as a form of social assistance to the community. If we look at the word sadaqah, it is taken from the Arabic word which means "justification", so alms is a form of self-justification for the existence of Islam. By embracing a democratic system, Indonesia cannot be separated from Islamic values, especially regarding human life socially. So the aim of this research is to analyze the role of Religious Courts in realizing the effectiveness of the state alms concept. The research method used is library research, data was collected by referring to publications on alms conflicts in religious courts and other scientific works. The results of the research show that the role of religious courts in matters of sadaqah is very, very important as supervisors and as mediators or places to resolve cases that arise regarding problems regarding sadaqah. The authority of the religious court in this matter is absolute and binding and each party must follow the series of courts and must follow every decision of the religious court.